Propagation Characteristics of Electromagnetic Waves in Multilayered Biological Human Tissue - Fayyadh H. Ahmed (Zanco Journal of Pure and Applied Sciences, 2021)
This paper uses CST-2014 software package and Matlab 2018b to provide the data required to analyze the propagation mode characteristics of the electromagnetic waves (EM) inside multilayered tissue structure such as tissue layer impedance (Z) and tissue layers interface reflection coefficient (K). Moreover, the paper presents the distribution behavior of the electrical field (E-Field) and specific absorption rate (SAR) inside multilayered tissue. The results show that the value of K is of the order of 0.7 at the air-skin interface, but it is about 0.1 at the tissue-tissue interface. The results also reveal that the SAR is directly proportioned to the frequency; in contrast, the standing wave (SW) of the E-filed is inversely proportioned with frequency. Three multilayered phantoms (body-shell, thyroid, and testis) were adopted, and the results were obtained at three resonant frequencies over the ultra-wideband (UWB) frequency span of 3GHz, 6.5GHz, and 10GHz. The simulation results proof the computational formulas.